Akurasi Presentasi Web dengan Animasi Scalable Vector Graphics: Studi Kasus Animasi Pembelajaran Komunikasi bagi Anak Autis - Taryadi Taryadi; Sattriedi Wahyu Binabar; Era Yunianto (Proceedings Series on Physical & Formal Sciences, 2021)
In recent years, the use of the Web to quickly and efficiently run behavioral and social experiments has grown in popularity. However, there are still revenue differences related to the use of the Web for animation and multimedia. The analysis and accuracy of the use of web technology have been widely studied to update evidence on the accuracy and precession of presenting animation using the Web, as well as expanding research related to accuracy and precision in the presentation of multimedia and animation based on HTML5 technology, especially the use of scalable vector graphics (SVG). Presentation of visual content using web technology can be accepted with increasing accuracy and precision, although this technology needs consideration in some cases in its use. Accuracy and precision using CSS technology which is part of HTML, are the best alternatives for animation. The animation interval is above 50 milliseconds based on test results, while testing using SVG also shows results that are not much different from using CSS in animation. The performance of procedural web technology with HTML5 standards (CSS, SVG, and WebGL) is not much different from the analyzed web technology, with an average missed frame between 0.06 and 1.50 with a standard deviation between 0.252 and 1.055. This technology is becoming the standard and has a promising future, making its use more advisable than other technologies on the decline.